Spectrophotometric evaluation of the color changes of different feldspathic porcelains after exposure to commonly consumed beverages - Jain, Chandni; Bhargava, Akshay; Gupta, Sharad; Rath, Rishi; Nagpal, Abhishek; Kumar, Prince (European Journal of Dentistry, 2013)
Objective: The aim of this study was to compare color stability and surface topography of three different feldspathic porcelains both qualitatively and quantitatively after exposure to routinely consumed beverages over different time periods using a Spectrophotometer, Stereomicroscope and Surface roughness tester, respectively. Materials and Methods: A total of 90 plastic discs were casted to obtain metal dies for three different newer ceramic applications each on thirty samples. The color and surface roughness of these samples were measured using stereomicroscope and surface roughness tester following which they were kept in different test solutions for different durations and revaluated for color changes and surface roughness in the similar manner. Results and Conclusion: Among all the five test solutions, Coffee showed the maximum staining of the ceramic whereas maximum surface roughness was shown by the Duceram Kiss (1.48 μm) by Orange Juice which could be due to its high titratable acidity.
Keywords: Color stability; feldspathic porcelains; spectrophotometer